2015
DOI: 10.2214/ajr.14.12681
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MRI-TRUS Fusion Versus Cognitive Registration Accuracy for MRI-Targeted, TRUS-Guided Prostate Biopsy

Abstract: MRI-targeted TRUS-guided prostate biopsy using cognitive registration appears to be inferior to MRI-TRUS fusion, with fewer than 50% of clinically significant PCA lesions successfully sampled. No statistically significant difference in biopsy accuracy was seen according to operator experience with prostate MRI or MRI-TRUS fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 38 publications
3
51
0
6
Order By: Relevance
“…In the other study, a software-based targeted strategy detected more clinically significant cancers than did a cognitive strategy, 20.3% vs. 15.1%, respectively (P ¼ 0.05) [13]. Another simulation study suggested that this difference might be wider, and more than 50% clinically significant cancer detected by software-based targeted biopsy might be missed by visually directed targeted biopsy [14]. Finally, software-based targeted biopsies may have an additional advantage in that images with prior sampling designated on them are stored so that further biopsies at a different time of the same areas are possible.…”
Section: Discussionmentioning
confidence: 90%
“…In the other study, a software-based targeted strategy detected more clinically significant cancers than did a cognitive strategy, 20.3% vs. 15.1%, respectively (P ¼ 0.05) [13]. Another simulation study suggested that this difference might be wider, and more than 50% clinically significant cancer detected by software-based targeted biopsy might be missed by visually directed targeted biopsy [14]. Finally, software-based targeted biopsies may have an additional advantage in that images with prior sampling designated on them are stored so that further biopsies at a different time of the same areas are possible.…”
Section: Discussionmentioning
confidence: 90%
“…MRI-targeted, TRUS-guided biopsy is likely best performed through fusion of MRI to 3D TRUS (MRI-TRUS fusion) rather than attempting to cognitively infer the MRI lesion location on standard non-fusion TRUS. 5,[14][15][16] While MRI-guided and MRI-TRUS fusion approaches have merit, MRI-TRUS fusion biopsy (Fn-Bx) allows for real-time needle visualization and can be performed in a clinical setting using a standard 2D TRUS probe incorporated into a 3D system, 13 rather than in an MRI suite with specialized MRI-compatible hardware. 8 Fn-Bx has demonstrated higher per-core CaP detection rates, higher Gleason grades, and higher percentage of tumour involvement within targeted cores as compared to systematic biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…Where TRUS is used to guide targeted biopsy, electronic fusion of magnetic resonance images with TRUS images can be performed to guide biopsy (14,15), or "cognitive fusion" can be used (16), by which the operator prospectively reviews the MRI appearances and uses TRUS to guide targeted sampling of the area of suspected tumor in the prostate gland.…”
mentioning
confidence: 99%